Servqual dan Conjoint Analysis Dalam House of Quality Untuk Layanan Ojek Online - Desrina Yusi Irawati; Octavia Ezrani (Jurnal Teknik Industri, 2018)
One of the transportation services that need quality improvement is an online motorcycle taxis. Integration Servqual and conjoint analysis in QFD process can determine the attributes of consumer needs, and technical response as an effort to improve the service motorcycle taxi online. The result of attributes combination of motorcycle taxi online service as a whole according to customer requirement are the attention of motorcycle taxi online, information system (application), waiting for the time of arrival, completeness of attribute while driving, as well as security and safety guarantee. From the result of QFD, the overall technical response that needs to be done to reach customer needs is online facility to absorb customer feedback, longer service period, and improvement of communication procedure with customers. It is formed by two segments of the customers of motorcycle taxi online namely the segment of empathy and responsiveness.